Pengaruh Peluang Bisnis di Era Pandemi dan Preferensi Risiko Terhadap Minat Berwirausaha Mahasiswa Jurusan Akuntansi Universitas Islam Malang - Rosalina Dwi Amara; Moh. Amin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to (1) identify and explain the effect of business opportunities in the pandemic era and risk preferences on student entrepreneurship interest (2) identify and explain the effect of business opportunities in the pandemic era on student entrepreneurship interest (3) identify and explain the effect of risk preference on student interest in entrepreneurship. The research method used in this study is a quantitative method, namely by distributing questionnaires to students majoring in accounting at the Islamic University of Malang. The number of respondents from the questionnaire distributed was 78 respondents. The results of this study indicate that business opportunities in the pandemic era and risk preferences have a positive effect on the interest in entrepreneurship of students majoring in accounting at the Islamic University of Malang.Keywords: Business opportunities in the pandemic era, risk preference, interest in entrepreneurship